Reproductive biology of Astyanax lacustris (Characiformes: Characidae) in the southern Pantanal floodplain, upper Paraguay River basin, Brazil - Súarez, Yzel R.; Silva, Edileia A.; Viana, Lucilene F. (Environmental biology of fishes, 2017)
We studied the reproductive biology of Astyanax lacustris in the southern Pantanal, Brazil. A total of 382 fish were analyzed from February 2009 to January 2011. The sex ratio differed significantly from 1:1, with a larger proportion of females (χ 2 = 27.24; p < 0.001). Females achieve higher standard length than males (mean 72.30 mm and 56.51 mm, respectively), and possess negative allometric growth while males have positive allometric growth. Size at first maturation did not differ between sexes. The greatest reproductive activity occurred during the rainy season, when temperatures were highest (November to February). Total fecundity was significantly correlated with standard length (r s = 0.74; p = 0.01), and spawn type was total. Then, the life history traits of A. lacustris are adjusted to seasonal variation in the Southern Pantanal.